2018
DOI: 10.1080/01694243.2018.1472427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temperature changes in the pulp chamber during polymerization of pulp capping materials

Abstract: Polymerization of resin-based materials leads to temperature rise, caused by the exothermic nature of the reaction and energy absorbed during polymerization. This temperature rise is influenced by intensity of light, composition of resins, and type of light source. This study evaluated thermal insulating properties of four photo-polymerizing pulp-capping agents in primary and permanent teeth. Roots of 80 primary and permanent teeth were removed. Class-I cavities were prepared on the occlusal surfaces of teeth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Our results showed that the chemically-cured lining material does not increase the temperature in the pulp chamber when it is placed over a direct pulp capping material. Temperature changes during liner light-curing elevated the pulp chamber temperature in the range of 5 -8.5 °C, which was comparable to temperature changes during light-curing of lining materials in previous studies [21,22,26]. This finding indicates that about 0.5 mm pulp exposure closed with any of the clinically recommended pulp capping materials sustains a comparable thermal challenge to the pulp as a liner-protected deep cavity without the pulp exposure.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our results showed that the chemically-cured lining material does not increase the temperature in the pulp chamber when it is placed over a direct pulp capping material. Temperature changes during liner light-curing elevated the pulp chamber temperature in the range of 5 -8.5 °C, which was comparable to temperature changes during light-curing of lining materials in previous studies [21,22,26]. This finding indicates that about 0.5 mm pulp exposure closed with any of the clinically recommended pulp capping materials sustains a comparable thermal challenge to the pulp as a liner-protected deep cavity without the pulp exposure.…”
Section: Discussionsupporting
confidence: 78%
“…Temperature changes ranging between 1.8 and 9.5 °C during light-curing of various lining materials (light-cured resin-based calcium-hydroxyde, calcium-silicate, calcium-hydroxyphosphate and glass ionomer cements) were previously reported for specimens with 1 mm of the remaining dentin thickness [21,22,26]. Our results showed that the chemically-cured lining material does not increase the temperature in the pulp chamber when it is placed over a direct pulp capping material.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation